Dinitrogen Cleavage and Hydrogenation by a Trinuclear Titanium Polyhydride Complex - Shima, Takanori; Hu, Shaowei; Luo, Gen; Kang, Xiaohui; Luo, Yi; Hou, Zhaomin (Science (American Association for the Advancement of Science), 2013)
Both the Haber-Bosch and biological ammonia syntheses are thought to rely on the cooperation of multiple metals in breaking the strong N=N triple bond and forming an N-H bond. This has spurred investigations of the reactivity of molecular multimetallic hydrides with dinitrogen. We report here the reaction of a trinuclear titanium polyhydride complex with dinitrogen, which induces dinitrogen cleavage and partial hydrogénation at ambient temperature and pressure. By ¹H and ¹⁵N nuclear magnetic resonance, x-ray crystallographic, and computational studies of some key reaction steps and products, we have determined that the dinitrogen (N₂) reduction proceeds sequentially through scission of a N₂ molecule bonded to three Ti atoms in a μ-η¹:η²:η²-end-on-side-on fashion to give a μ₂-N/μ₃-N dinitrido species, followed by intramolecular hydrogen migration from Ti to the μ₂-N nitrido unit.